Prevalence and risk factors of Coxiella burnetii infection in cattle on farms in Limpopo province, South Africa - Adesiyun, Abiodun Adewale (University of Pretoria, 2023)
Dissertation (MSc (Production Animal Studies))--University of Pretoria, 2022.